VirTraM: Um framework para o desenvolvimento de treinamentos utilizando realidade virtual em dispositivos móveis - Barros Filho, Edgar Marçal de (2005)
Mobile computing has emerged as an innovative technology for education. For example, a new terminology, called Mobile Learning or m-Learning, has been introduced to designate the use, in a transparent way and with a high mobility degree, of devices with wireless communication, as part of a model of integrated learning, On the other hand, education can be also seen as a process of exploration, discovery and construction of knowledge, using three-dimensional environments. However, different challenges are faced when designing educational applications for mobile devices with three-dimensional resources, such as: How to produce a 3D scenario together with images and information in the reduced screens of cellular phones? How to make possible efficient ways of interaction? How to overcome the limitation of memory and processing of the mobile devices? In this master's thesis, a framework for the development of educational applications with virtual reality resources in mobile devices is introduced, called VirTraM. This framework facilitates the development of such applications, allowing a programmer to work with little elements, abstracting the implementation details and emphasing the aspects concerning the training. For the validation of VirTraM, two case studies have been developed. These case studies demonstrate such characteristics as interaction, usability and portability, besides making possible the integration of mobile computing and virtual reality technologies. An application, constructed from VirTraM, offers to the user an innovative and interactive tool to help with complementary information at the moment and place where his necessary. Amongst the benefits of the applications based on VirTraM, the following are distinguished: to support and to motivate the learning; to improve the understanding on definitive objects; to allow the simulation and analysis of experiences in the field; to make possible the demonstration of the equipment execution; and to provide ways for the development of innovative methods of education and training.